Effect of psychological intervention combined with nutritional support under PERMA model on psychological resilience, cancer-related fatigue and nutritional status in patients with esophageal cancer undergoing radiotherapy and chemotherapy (PERMA模式下心理干预联合营养支持对食管癌放化疗患者心理弹性、癌因性疲乏及营养状况的影响) - HU Mengli (胡梦丽); Li Shuhua (李淑华) (Journal of International Translational Medicine Limited, 2022)
Objective To explore the effect of psychological intervention combined with nutritional support under the PERMA ［Positive Emotion (P), Engagement (E), Relationships (R), Meaning (M), Achievement (A)］ model on the psychological resilience, cancer-related fatigue, nutritional status and quality of life in patients with esophageal cancer undergoing radiotherapy and chemotherapy. Methods Totally 100 patients with esophageal cancer admitted to the hospital between January 1, 2020 and January 1, 2021 were selected as the research subjects. According to the random method, the research subjects were divided into control group (49 cases) and observation group (51 cases). The control group received routine intervention, and the observation group was given psychological intervention combined with nutritional support under PERMA model, and the two groups were intervened for 3 months. After 3 months, the scores of Connor-Davidson Psychological Resilience Scale (CD-RISC), Fatigue Scale-14 (FS-14), and Fatigue Scale-14 (FS-14). Nutrition Status Assessment Scale (MNU-ST) and Quality of Life Scale (SF-36) were observed in the two groups of patients. Results ①In the three dimensions of toughness, strength and optimism of CD-RISC scale, the psychological resilience of the two groups of patients was improved after intervention, and scores of observation group were higher than those of control group (P<0. 05). ②After intervention, the scores of physical fatigue and mental fatigue of FS-14 scale were lower in observation group than those in control group (P<0. 05). ③The proportion of patients with good nutritional status of MNU-ST in observation group after intervention was greater than that in control group (P<0. 05). ④After intervention, the scores of four aspects of SF-36 scale such as body pain, health status, vitality and social function were higher in observation group compared to control group (P<0. 05). Conclusion The implementation of psychological intervention combined with nutritional support under PERMA model can increase psychological resilience, reduce fatigue, improve nutritional status and enhance quality of life of patients with esophageal cancer undergoing radiotherapy and chemotherapy. In addition, it is of great significance for improving clinical nursing measures. (目的 探究在PERMA［积极情绪(P)、投入(E)、人际关系(R)、意义(M)、成就(A)］模式下对食管癌放化疗患者实施心理干预联合营养支持对心理弹性、癌因性疲乏、营养状况及生活质量的影响。方法 选取医院2020年1月1日-2021年1月1日收治的100例食管癌患者为研究对象, 随机分为对照组49例和观察组51例。对照组采取常规干预, 观察组采取PERMA模式下心理干预联合营养支持, 干预时间3个月, 3个月后观察两组患者心理弹性量表(CD-RISC)、疲劳量表-14(FS-14)、营养状况评估表(MNU-ST)、生活质量量表(SF-36)情况。结果 ①CD-RISC: 在坚韧性、力量性、乐观性这三个维度上, 两组患者干预后心理弹性均好转, 且观察组评分高于对照组 (P＜0. 05)。②FS-14: 干预后观察组躯体疲劳、脑力疲劳维度评分低于对照组患者(P＜0. 05)。③MNU-ST: 干预后观察组MNU-ST营养状况良好人数占比大于对照组患者(P＜0. 05)。④SF-36: 干预后观察组机体疼痛、健康状况、活力、社会功能维度评分高于对照组(P＜0. 05)。结论 实施PERMA模式下心理干预联合营养支持可提升食管癌放化疗患者心理弹性、降低疲乏程度、改善营养状况和提升生活质量, 对于改进临床护理措施具有重要意义。)